2019
DOI: 10.7897/2230-8407.1004152
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antidiabetic Activity and Phytochemical Analysis of Lumnitzera Racemosa Leaves

Abstract: The present study was designed to evaluate the antidiabetic property and phytochemical composition of Lumnitzera racemosa leaves. Mangrove plant L. racemosa was collected in the month of May from Bhatye beach area Ratnagiri coast, Maharashtra, India. Leaves separated, powdered and exhaustive extraction was carried out in methanol, ethanol, ethyl acetate, and pet ether solvents with increasing polarity using Soxhlet apparatus and in vitro antidiabetic activity was determined by α-amylase and α-glucosidase inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In our earlier study, we found L. racemosa to be a potent inhibitor of α-amylase and α-glucosidase enzymes in vitro and a rich source of secondary metabolites like alkaloid, flavonoid, and saponin as well which are proved to possess antidiabetic activity. 12 So in continuation of our previous work, the present study has been undertaken to isolate an antidiabetic principle from L. racemosa leaves and evaluate its antidiabetic efficacy in vivo on Streptozotocin-induced Wistar rats. Thus, a bioactive compound was isolated from L. racemosa which is characterized as an alkaloid, named 4a-methyl-5-(6-methylhept-5-en-1-yl)octahydro-1Hcyclopenta[a] pyridazine (MOCP).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In our earlier study, we found L. racemosa to be a potent inhibitor of α-amylase and α-glucosidase enzymes in vitro and a rich source of secondary metabolites like alkaloid, flavonoid, and saponin as well which are proved to possess antidiabetic activity. 12 So in continuation of our previous work, the present study has been undertaken to isolate an antidiabetic principle from L. racemosa leaves and evaluate its antidiabetic efficacy in vivo on Streptozotocin-induced Wistar rats. Thus, a bioactive compound was isolated from L. racemosa which is characterized as an alkaloid, named 4a-methyl-5-(6-methylhept-5-en-1-yl)octahydro-1Hcyclopenta[a] pyridazine (MOCP).…”
Section: Discussionmentioning
confidence: 94%
“…All three fractions were tested for their in vitro antidiabetic activity, which was estimated by α-amylase and α-glucosidase inhibition assays by following the method mentioned in our previous report. 12…”
Section: In Vitro Antidiabetic Activitymentioning
confidence: 99%
See 1 more Smart Citation